Markov process modeling for wireless sensor network availability with QOS constraints - Karimi, Abbas; Kiamanesh, B.; Zarafshan, Faraneh; Syed Mohamed, Syed Abdul Rahman Al-Haddad (Trans Tech Publications, 2013)
The purpose of this paper is calculating the availability of wireless sensor network for a virtual grid by using Markov model. Since, wireless sensor networks are constraints by energy, their energy consumption should be limited within a way to guarantee their quality of service. In this paper, availability and quality of service in a wireless sensor network with particular coverage are investigated by using an energy optimized algorithm and Markov process.